Nutrient release characteristics and coating homogeneity of biopolymer coated urea as a function of fluidized bed process variables - Azeem, B. (Wiley-Liss Inc., 2017)
The present study investigates the effect of fluid-bed process parameters on the diffusion coefficient of nitrogen release and coating homogeneity of controlled-release urea (CRU) produced in a rotary fluidized bed using polyvinyl-alcohol-modified starch as a coating material. An existing mathematical model was used to estimate the diffusion coefficient. The coefficient of variance of size distribution and coating mass variation are reported as a measure of coating homogeneity. Statistical analysis suggested that the most influential process variables that govern urea release characteristics and coating homogeneity were (a) fluidizing gas temperature and (b) coating time. A moderate spray rate combined with longer coating time yielded the lowest diffusion coefficient for nutrient release. Elutriation as the result of elevated fluidizing gas temperature allowed a higher diffusion coefficient due to lower coating thickness. Burst release patterns were observed for granules with coating imperfections. The augmented temperature of fluidizing gas had a negative effect on coating mass and size distribution of CRU granules but the influence of longer coating time was positive. © 2016 Canadian Society for Chemical Engineering